Blood Pressure Coefficient of Variation and Its Association With Cardiac Surgical Outcomes. (October 2018) - Jinadasa, Sayuri P.; Mueller, Ariel; Prasad, Varesh; Subramaniam, Kathirvel; Heldt, Thomas; Novack, Victor; Subramaniam, Balachundhar
Abstract : BACKGROUND: Multiple studies completed in the ambulatory nonsurgical setting show a significant association between short- and long-term blood pressure variability and poor outcomes. However, perioperative blood pressure variability outcomes have not been well studied, especially in the cardiac surgical setting. In this study, we sought to assess whether systolic and mean arterial blood pressure variability were associated with 30-day mortality and in-hospital renal failure in patients undergoing cardiac surgery requiring cardiopulmonary bypass. Furthermore, blood pressure variability has not been evaluated specifically during each phase of surgery, namely in the pre-, intra- and postbypass phases; thus, we aimed also to assess whether outcomes were associated with phase-specific systolic and mean arterial blood pressure variability. METHODS: All patients undergoing cardiac surgery from January 2008 to June 2014 were enrolled in this retrospective, single-center study. Demographic, intraoperative, and postoperative outcome data were obtained from the institution's Society of Thoracic Surgery database and Anesthesia Information Management System. Systolic and mean arterial blood pressure variability were assessed using the coefficient of variation (CV). The primary outcomes were 30-day mortality and in-hospital renal failure in relation to the entire duration of a case, while the secondary outcomes assessed phase-specific surgical periods. In an effort to control the family-wise error rate, P values <.0125 were considered significant for the primary outcomes. RESULTS: Of the 3687 patients analyzed, 2.7% of patients died within 30 days of surgery and 2.8% experienced in-hospital renal failure. After adjusting for significant covariates, we found a statistically significant association between increasing CV for systolic blood pressure (CVSBP ) and 30-day mortality and in-hospital renal failure. For every 0.10 increase in CVSBP, there was a 150% increase in the odds of death (odds ratio, 2.50; 95% confidence interval, 1.60–3.92; P < .0001) and there was a 104% increase in odds of experiencing renal failure (odds ratio, 2.04; 95% confidence interval, 1.33–3.14; P = .001). The association with mortality was driven primarily by the prebypass period, because the association between CVSBP and mortality during the prebypass phase was significant ( P = .01), and not during the postbypass phase ( P = .08). There was no significant association between CV for mean arterial blood pressure and either death or renal failure during any period of surgery, including the bypass phase. CONCLUSIONS: Increasing systolic blood pressure variability was associated with 30-day mortality and development of renal failure, with surgery phase-specific relationships observed. Further research is required to determine how to prospectively detect blood pressure variability and elucidate opportunities for intervention.